Lipoprotein Insulin Resistance Index Reflects Liver Fat Content in Patients With Nonalcoholic Fatty Liver Disease. Issue 4 (29th December 2020) - Vittal, Anusha; Shapses, Mark; Sharma, Bashar; Sharma, Disha; Sun, Qian; Sampson, Maureen; Lee, Wilson; Ben Yakov, Gil; Rotman, Yaron
Abstract : The recently developed lipoprotein insulin resistance index (LP‐IR) incorporates lipoprotein particle numbers and sizes and is considered to reflect both hepatic and peripheral IR. As tissue IR is a strong component of nonalcoholic fatty liver disease (NAFLD) pathogenesis, we aimed to assess the degree by which LP‐IR associates with hepatic fat content. This was a single‐center retrospective analysis of patients with NAFLD. LP‐IR, the homeostasis model assessment of insulin resistance (HOMA‐IR), and adipose tissue IR (Adipo‐IR) were measured simultaneously. Liver fat content was estimated by FibroScan controlled attenuated parameter. Associations were assessed using Spearman's correlation and multivariate linear regression. The study included 61 patients. LP‐IR was correlated with HOMA‐IR (ρ = 0.30; P  = 0.02), typically thought to reflect hepatic IR, but not with Adipo‐IR (ρ = 0.15; P  = 0.25). Liver fat content was significantly associated with Adipo‐IR (ρ = 0.48; P  < 0.001), LP‐IR (ρ = 0.35; P  = 0.005), and to a lesser degree with HOMA‐IR (ρ = 0.25; P  = 0.051). The association of liver fat with LP‐IR was limited to patients without diabetes (ρ = 0.60; P  < 0.0001), whereas no association was seen in those with diabetes. In a multivariate model, Adipo‐IR, LP‐IR, and diabetes were independently associated with liver fat and together explained 35% of the variability in liver fat. Conclusion: LP‐IR is a reasonable measure of IR in non‐diabetic patients with NAFLD and is associated with hepatic fat content. Although adipose tissue is the major contributor to liver fat, the additional contribution of nonadipose tissues can be easily estimated using LP‐IR.